Implementasi Metode K-Medoids Dalam Pengelompokan Kepuasan Masyarakat Terhadap Pelayanan Rumah Sakit - Handayani, Tri; Bahri, Syamsul; Kasliono, Kasliono (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Service is an effort made to meet customer's direct needs with the aim of helping their needs. One of the institutions that provides services in the health sector is a hospital. The public satisfaction survey aims to assess the level of public satisfaction with service quality to improve it. Assessment of public satisfaction with service quality can vary. With these diverse survey results, a system is needed that supports grouping public satisfaction with services. In this research, the K-Medoids method is used to classify public satisfaction with services. The variables used for grouping consist of service requirements, service procedure systems and mechanisms, service time, costs/tariffs, product specifications, types of service, competence of implementers, behavior of implementers, quality of facilities and infrastructure, and complaint handling. This research resulted in different categories, such as very good, good, poor and not good. The criteria for measuring the results of K-Medoids using the Silhouette Coefficient from the results of 26 experimental data obtained the best evaluation results with a value range of 0.9 – 1.00 which is included in the criteria for a strong structure with total cluster of 4. The results of 400 data that have been implemented into the web-based system on the 26 experimental data described above, from the results of each cluster for each iteration it can be concluded that the community's satisfaction with the services at RSUD Dr. Soedarso Pontianak, from the sum of the results of 9.365 cluster members from all iterations, is in cluster 4 with the very good category.